2016
DOI: 10.5937/bankarstvo1604070k
|View full text |Cite
|
Sign up to set email alerts
|

The influence of foreign direct investments on economic and social development of Serbia

Abstract: Foreign direct investments have gained prominence in the world during the past several decades. This article explores the factors which have influenced the attraction of foreign direct investments, and the influence of foreign direct investments on economic and social development and the international integration of the Republic of Serbia. Foreign direct investments' flows, structure and effects have been analyzed, by using secondary sources of data and by applying a number of methods, such as historical, desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Namely, export effects appear to be strongly positive in developing countries (Ahmad et al, 2018; Asirvatham et al, 2017; Mijiyawa, 2017; Sahoo & Dash, 2022). The existing macro‐level studies focusing on Serbia are in line with these findings, indicating a significant positive correlation between foreign direct investment and exports of moderate intensity (Kastratović, 2016; Obradović et al, 2021). In contrast, the effects are mainly insignificant in developed countries (Acaravci & Ozturk, 2012; Popovici, 2018).…”
Section: Literature Reviewsupporting
confidence: 59%
“…Namely, export effects appear to be strongly positive in developing countries (Ahmad et al, 2018; Asirvatham et al, 2017; Mijiyawa, 2017; Sahoo & Dash, 2022). The existing macro‐level studies focusing on Serbia are in line with these findings, indicating a significant positive correlation between foreign direct investment and exports of moderate intensity (Kastratović, 2016; Obradović et al, 2021). In contrast, the effects are mainly insignificant in developed countries (Acaravci & Ozturk, 2012; Popovici, 2018).…”
Section: Literature Reviewsupporting
confidence: 59%
“…A similar trend was recorded in FDIs as well. The FDIs inflow was very high after 2003, especially in the period 2006-2008(Stojanović, 2018Kastratović, 2016).…”
mentioning
confidence: 99%
“…The same analysis showed that total imports had the largest impact on BiH's economic growth, while foreign direct investments and total exports took second place. The general conclusion, based on all the aforementioned and other empirical research, is that FDI does have a positive impact on GDP growth, exports, and foreign currency inflow, as well as on the decrease of unemployment, poverty, and inequality (Kastratović, 2016).…”
Section: Literature Overviewmentioning
confidence: 91%